Synthesis, Spectroscopic Investigation of Phytochemicals for antibacterial efficacy of Gardenia latifolia - Bharti, Nirvani; Sharma, Renu; Brar , Basanti (Journal of Neonatal Surgery, 2025)
Introduction: Gardenia latifolia, commonly referred to as Indian boxwood or Ceylon boxwood, is a traditional medicinal plant historically used in India to treat various human diseases. From the past few decades it has been traditionally recognized that Gardenia latifolia acts as an effective agent in such as snake bites, skin issues, stomach pains, inflammatory discomfort, dental caries, bleeding in humans, and ephemeral fevers in livestock along with it acts as an excellent painkiller as well as an antiseptic for healing wounds. In the present study we investigated the phytochemicals of bark plant extract of Gardenia latifolia and its antibacterial activity. Materials and Methods: The present work deals with synthesis and characterization of important organic constituents of Gardenia latifolia. The first step of synthesis process involves the collection of plant. For the selection of solvent systems for phytochemicals extraction from G. latifolia has been done using hexane, chloroform, ethyl acetate and methanol. Results: Bioactive flavonoids, saponins, terpenoids and phenols have been isolated from the stem bark extract Gardenia latifolia for phytochemical investigation. Phytochemical structures were elucidated from obtained spectral data by FTIR spectra and UV-Visible spectra and anti-bacterial study. In FTIR Spectra shows the absorption bands pertinent to -OH stretching showed the presence of hydroxyl groups, the presence of phenolic compounds in methanolic and ethyl acetate extract of G. latifolia. UV-Vis spectroscopic confirms the presence of tannins and flavonoids in the methanolic and ethyl acetate extract of G. latifolia. Conclusion: The methanol extract of G. latifolia, with bioactive compounds, is a promising source of lead compounds for future drug development.